The City Symphony Phenomenon - Jacobs, Steven. (Milton)
1 online resource (410 p.).
Keywords: The 1920s and 1930s saw the rise of the city symphony, an experimental film form that presented the city as protagonist instead of mere decor. Combining experimental, documentary, and narrative practices, these films were marked by a high level of abstraction reminiscent of high-modernist experiments in painting and photography. Moreover, interwar city symphonies presented a highly fragmented, oftentimes kaleidoscopic sense of modern life, and they organized their urban-industrial images through rhythmic and associative montage that evoke musical structures.In this comprehensive volume, contributors consider the full80 film corpus,fromManhattaand Berlin: Die Sinfonie der Grosstadt to lesser-known cinematic explorations.